Method Used In Teaching Reading At The Second Year Of SMK Muhammadiyah 4 Surakarta - Setyawati, Susanti Ika (2012)
This research paper is intended to describe the method used by the English teacher of SMK Muhammadiyah 4 Surakarta at the second year in teaching reading. The objectives of the study are to describe the approach used by the English teacher in teaching reading, to describe the design of method used by the English teacher in teaching reading and to describe the procedure of teaching learning process. The type of this research is Qualitative research. In this research, the data are derived from event, informant, and document. There are three methods of colleting data namely: observation, interview, and document analysis. The result of this research show that the teacher used Humanism approach in teaching reading at the second year of SMK Muhammadiyah 4 Surakarta. The method used by teacher is Communicative Language Teaching. The use of Communicative Language Teaching can improve the student reading skill, because, this approach makes the students to be active in their class. They can find the problem and solve by themselves, they can work together and have group discussion, so the teaching learning process is not bored and joyful. Based on the research, the writer has come to the conclusion that there are some strengths and weeknesses in teaching reading by used Communicative Language Teaching. The students and the teacher can communicate each other by using the target language. Thus, the material taught can facilitate communication activities, such as interpretation, expression and negotiation, and the students in SMK Muhammadiyah 4 Surakarta will have communicative competence. The weaknesses of Communicative Language Teaching in SMK Muhammadiyah 4 Surakarta that in only focused in teaching-learning process and the little interaction among the students in teaching learning process that can influence the mastery of the target language.